2005
DOI: 10.1248/cpb.53.32
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Evaluation of 1-Substituted 1,2,3,4-Tetrahydro- and 3,4-Dihydro-.BETA.-carboline Derivatives as Potential Antitumor Agents

Abstract: Marine natural products which contain a b-carboline skeleton are widely distributed in marine invertebrates. 1-3)The discovery of natural b-carboline metabolites as potent antitumor and antiviral agents has stimulated great interest in the synthetic and pharmacological studies of b-carboline derivatives. [4][5][6] Particularly interesting targets include such compounds as eudistomins 7,8) and manzamines, 9,10) which were isolated from marine tunicates and sponges, respectively. As a class, the oxathiazepine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…It should be noted that spectra of compounds 5a,b lacked signals due to secondary amino group protons, which is characteristic for the spectra of β-carbolines [16,17].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…It should be noted that spectra of compounds 5a,b lacked signals due to secondary amino group protons, which is characteristic for the spectra of β-carbolines [16,17].…”
mentioning
confidence: 90%
“…The most intense signals (I rel = 100%) were produced by ions due to elimination of a CO molecule from molecular ions (for compounds 3a and 5a), a CO molecule and methyl radical (for compounds 3b, 4b, 5b, and 6b), a methyl radical and two CO molecules (for compounds 4a and 6a) [11,15,17].…”
mentioning
confidence: 99%
“…Recently, a series of 1,2,3,4-tetrahydro-β-carboline derivatives were reported to be CDK4-specific inhibitors (Aubry et al, 2006), which may cause G1 arrest of tumor cells. Several 1-aryl substituted 1,2,3,4-tetrahydro-β-carboline derivatives also showed significant cytotoxicity against murine P-388 and human tumor cell lines, KB-16, A-549, and HT-29 (Shen et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Studies on structure-activity relationship have demonstrated the influence of the substituents in positions-1, -3, and -9 of the b-carboline skeleton for a variety of synthetic b-carboline derivatives [10][11][12][13][14][15][16][17][18][19]. Furthermore, antiviral activity has been reported for several compounds possessing the carbohydrazide moiety [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Druglikeness and drug-score values of the most active compounds(6,7,10,11,12) and Acyclovir (ACV) using Osiris program.6.71 (2H, d, J ¼ 7.5 Hz, H-3 0 /H-5 0 ), 7.71-7.58-7.66 (5H, m, Ar-H), 7.80 (2H, d, J ¼ 8.0 Hz, H-2 00 /H-6 00 ), 8.07 (2H, d, J ¼ 7.5 Hz, H-2 0 /H-6 0 ), 8.26 (1H, d, J ¼ 7.8 Hz, H-5), 8.39 (1H, s, N]CH), 9.13 (1H, s, Yield: 83%; mp: 310-312 C; IR (KBr) n max (cm À1 ): 3304 (N-H), 1657 (C]O), 1534-1314 (C]C); 1 H NMR (300 MHz, CDCl 3 /CD 3 OD): d 7.15 (2H, d, J ¼ 7.8 Hz, H-3 0 /H-5 0 ), 7.37 (1H, t, J ¼ 7.8 Hz; H-6), 7.55-7.40 (3H, m, Ar-H), 7.66 (1H, d, J ¼ 7.8 Hz, H-8), 7.84 (2H, d, J ¼ 7.8 Hz, H-2 0 /H-6 0 ), 7.95 (2H, d, J ¼ 8.0 Hz; H-2 00 /H-6 00 ), 8.27 (1H, d, J ¼ 8.0 Hz, H-5), 8.33 (1H, s, N]CH), 8.93 (1H, s, H-4); 13 C NMR (CDCl 3 /CD 3 OD): d 112.Hydroxyphenyl)-N 0 -(4-nitrobenzylidene)-9H-pyrido[3,4-b]indole-3-carbohydrazide (8). Yield: 80%; mp: 342-344 C; IR (KBr) n max (cm À1 ): 3380 (N-H), 1675 (C]O), 1524-1310 (C]C); 1 H NMR (300 MHz, DMSO-d 6 ): d 7.08 (2H, d, J ¼ 7.5 Hz, H-3 0 /H-5 0 ), 7.35 (1H, t, J ¼ 7.5 Hz, H-6), 7.60 (1H, t, J ¼ 7.5 Hz, H-7), 7.73 (1H, d, J ¼ 7.5 Hz, H-8), 8.03 (2H, d, J ¼ 8.0 Hz, H-3 00 /H-5 00 ), 8.13 (2H, d, J ¼ 7.5 Hz, H-2 0 / H-6 0 ), 8.34 (2H, d, J ¼ 8.0 Hz, H-2 00 /H-6 00 ), 8.47 (1H, d, J ¼ 7.…”
mentioning
confidence: 99%